The role of genetic and hormonal factors in shaping exercise responses and performance in children: a comprehensive review: Genetics and hormones in child exercise - Zourmand, Gholamreza; Taheri, Morteza; Shaabani Ezdini, Ebrahim; Irandoust, Khadijeh (Cellular and Molecular Biology, 2025)
This review aims to explore the role of genetic and hormonal factors in shaping exercise responses and performance in children, providing insights into their implications for training and talent identification. A comprehensive narrative review of the literature was conducted, analyzing studies published between 2014 and 2024. The review focused on genetic predispositions, key hormones regulating exercise performance, and their combined influence on physical development in children. Data were collected from peer-reviewed journals and analyzed using a descriptive approach to identify patterns and practical applications in pediatric exercise science. The review highlights that genetic factors play a foundational role in determining physical attributes such as muscle composition, aerobic capacity, and metabolic efficiency. Key genes, including ACTN3 and ACE, have been linked to variations in strength, endurance, and recovery potential. Hormonal factors, particularly growth hormone, insulin-like growth factor-1, testosterone, and cortisol, dynamically influence exercise adaptation, with significant changes occurring during developmental stages. The interaction between genetic and hormonal influences suggests that personalized training approaches can optimize performance while considering developmental stages and environmental factors. Ethical considerations surrounding genetic testing for talent identification remain a critical concern, emphasizing the need for responsible and evidence-based application in pediatric sports programs. Therefore, it is crucial to understand the relationship between genetic and hormonal factors for designing individualized exercise programs that enhance athletic potential while ensuring long-term health and well-being. Future research should focus on integrating genetic and hormonal insights with environmental and behavioral factors to develop holistic training strategies for children.